1969
DOI: 10.1079/pns19690022
|View full text |Cite
|
Sign up to set email alerts
|

Digestion in the pre-ruminant animal

Abstract: The fore-stomachs of ruminant animals do not develop fully and assumc their characteristic digestive functions until the young animal begins to eat substantial quantities of solid food. When young calves consume liquid feed nearly all of it by-passes the reticulo-rumen and passes through the omasum into the abomasum as a result of the reflex closure of the oesophageal groove. The subsequent course of events during digestion in the abomasum and small intestinc has for long been regarded as being closely paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0
2

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 28 publications
2
9
0
2
Order By: Relevance
“…CP digestibility did not differ significantly between groups. The range of acid detergent fibre (ADF) digestibility was 7 to 20%, which is consistent with the findings of Porter (1969). The digestibility of nutrients depends on the development and capacity of the digestive tract (Roy, 1980;Thivend et al, 1980).…”
Section: Nutrient Intakesupporting
confidence: 77%
“…CP digestibility did not differ significantly between groups. The range of acid detergent fibre (ADF) digestibility was 7 to 20%, which is consistent with the findings of Porter (1969). The digestibility of nutrients depends on the development and capacity of the digestive tract (Roy, 1980;Thivend et al, 1980).…”
Section: Nutrient Intakesupporting
confidence: 77%
“…1977). This is understandable in view of the 473 in vitro results obtained in the present study and in previous work (Jenkins et al 1980 (Mylrea 1966;Porter 1969;Chow and Bell 1976 Fries and co-workers (1958) found that the addition of 0.57o pepsin to a milk replacer produced no improvement in growth of preruminant calves. The milk replacer, composed offinely ground corn, corn distillers' solubles, whey, skim milk and soybean flour, atypical by today's standards, was fed as a gruel.…”
supporting
confidence: 56%
“…Les sujets recevant la ration de There have been numerous unsuccessful attempts to substitute vegetable or fish proteins for milk proteins in liquid diets for preruminant calves (Porter 1969; Radostits and Bell 1970;Roy 1970). Many of the experiments were conducted with soybean products, with the cruder products giving the poorest calf performance (Roy 1970).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Hill et al 19'70;Roy 1970 Trypsin, chymotrypsin and carboxypeptidase are secreted into the small intestine of the calf via the pancreatic juice (Porter 1969). Each enzyme has good proteolytic activity within a pH range of I -9 (Boyer et al 1960 …”
mentioning
confidence: 99%